2001
DOI: 10.1001/archinte.161.19.2301
|View full text |Cite
|
Sign up to set email alerts
|

Rigorous New Approach to Constructing a Gold Standard for Validating New Diagnostic Criteria, as Exemplified by the Eosinophilia-Myalgia Syndrome

Abstract: The proposed criteria are accurate and reproducible, and can be used in future clinical investigations of the eosinophilia-myalgia syndrome. The new strategy and methods developed for this challenge can be valuable for solving analogous problems in constructing criteria for other clinical disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(32 citation statements)
references
References 34 publications
(31 reference statements)
0
32
0
Order By: Relevance
“…It was identified following an outbreak of the syndrome that was associated with the consumption of a certain brand of nutritional supplement containing tryptophan in the late 1980s. Hertzman et al (2001Hertzman et al ( , p. 2302 report that EMS has proved difficult to diagnose in epidemiological studies of the disease, and that suggested diagnostic criteria had not been validated. They sought to produce and validate a set of diagnostic criteria by measuring their diagnostic accuracy.…”
Section: Eosinophilia-myalgia Syndromementioning
confidence: 99%
See 4 more Smart Citations
“…It was identified following an outbreak of the syndrome that was associated with the consumption of a certain brand of nutritional supplement containing tryptophan in the late 1980s. Hertzman et al (2001Hertzman et al ( , p. 2302 report that EMS has proved difficult to diagnose in epidemiological studies of the disease, and that suggested diagnostic criteria had not been validated. They sought to produce and validate a set of diagnostic criteria by measuring their diagnostic accuracy.…”
Section: Eosinophilia-myalgia Syndromementioning
confidence: 99%
“…3 These patterns together functioned as criteria for the diagnosis of EMS, as the authors recommended that "EMS can be diagnosed if either pattern 1 or 2 is satisfied", so long as other potential causes of illness were first ruled out. "EMS should not be diagnosed in the presence of trichinosis, vasculitis, or any other documented infectious, allergic, neoplastic, connective tissue or other type of disease that could adequately explain the clinical manifestations" (Hertzman et al 2001(Hertzman et al , p. 2303.…”
Section: Eosinophilia-myalgia Syndromementioning
confidence: 99%
See 3 more Smart Citations